Microfiltration and ultrafiltration membranes for drinking water - Delphos, Paul J. (AWWA manual ;, 2016)
Microfiltration and ultrafiltration have gained rapid acceptance as processes that provide a reliable and very high level of particle, turbidity, and microorganism removal. This manual contains information on low pressure membranes in their widely diverse applications, operations and system designs.